Loja como icono en las artes vivas, sobres sus potencialidades y posibilidades para el festival internacional - Villamagua Jeamil, Burneo (2016)
This paper provides a current view on the development of the Loja's culture, specifically presents us with an analysis of the influence that is generated with the completion of the "First International Festival of Living Arts, Loja 2016". Starting from the traditional conception of the city of Loja as the epicenter of some artistic and identity demonstrations in the country, it is contrasted with urban and production criteria on the relevance ofcreating a cultural product that transcends realization of the festival, whose only identification and operation is and a tacit acceptance of some postulates mentioned herein. At the end it referred to some similar events that have been taken concerning the realization, emphasizing their pros and cons, likewise raised some recommendations and conclusions that have been generated from direct consultation in a focus group defined for this purpose interest.